Wealth Accumulation of Black and White Families: The Empirical Evidence - Terrell, Henry S. (Journal of Finance, 1971)
Henry S. Terrell, Wealth Accumulation of Black and White Families: The Empirical Evidence, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 363-377